Preoperative use of Granisetron Plus Dexamethasone and Granisetron Alone in Prevention of Post Operative Nausea and Vomiting in Tonsillectomy - Islam, MR; Haq, MF; Islam, MA; Meftahuzzaman, SM; Sarker, SC; Rashid, H; Rashid, HU (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):386-390 The abstract of this article is available on the PubMed website